2023
DOI: 10.1021/jacs.3c07506
|View full text |Cite
|
Sign up to set email alerts
|

How the Acidity of Water Droplets and Films Is Controlled by the Air–Water Interface

Miguel de la Puente,
Damien Laage

Abstract: Acidity is a key determinant of chemical reactivity in atmospheric aqueous aerosols and water microdroplets used for catalysis. However, many fundamental questions about these systems have remained elusive, including how their acidity differs from that of bulk solutions, the degree of heterogeneity between their core and surface, and how the acid−base properties are affected by their size. Here, we perform hybrid density functional theory (DFT)-quality neural network-based molecular simulations with explicit n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The combination of a continuous-flow setup and employing molecular entities as the sources of OEEFs , is another promising approach. Thus, for example, Zare et al , use water droplets, in which the O–H bonds on the surface of the droplet, as well as ions in the interface between droplets, deliver powerful OEEFs ,, that catalyze unusual reactions, with efficiency that increases with decrease in the diameter of the droplets .…”
Section: A Vision Of the Field In 2050: Scaling Up Oeef Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of a continuous-flow setup and employing molecular entities as the sources of OEEFs , is another promising approach. Thus, for example, Zare et al , use water droplets, in which the O–H bonds on the surface of the droplet, as well as ions in the interface between droplets, deliver powerful OEEFs ,, that catalyze unusual reactions, with efficiency that increases with decrease in the diameter of the droplets .…”
Section: A Vision Of the Field In 2050: Scaling Up Oeef Reactionsmentioning
confidence: 99%
“…Zare et al , showed that interfaces of water–air, water–solid, and water–oil generate water droplets which give rise to H 2 O 2 and other unusual products. Recently, Laage et al used molecular dynamic simulations and demonstrated that the droplet surface is acidic and contains excess H 3 O + ions. As such, the droplet surface generates a unique source of molecular electric field, which accelerates nucleophilic-cleavage reactions .…”
Section: Use Of Water Microdroplets To Accelerate Reactionsmentioning
confidence: 99%
“…With acidity recognized as a key determinant of reactivity in aqueous phases, considerable experimental and simulation efforts have been devoted to characterizing the acid–base properties of the air–water interface in recent decades. Although no definitive answer to this question has been obtained yet, there is accumulating evidence of substantial surface activity of hydronium (H 3 O + ) cations. , ,,, Among the experimental techniques that have supported this acid-enriched picture of the air–water interface, vibrational sum-frequency generation (SFG) spectroscopy has been instrumental because of its surface specificity. SFG measurements have revealed that the vibrational spectrum of the neat water surface changes markedly when the solution is acidified, , which has been suggested to arise from the presence of hydronium ions at the air–water interface.…”
mentioning
confidence: 99%
“…A series of 16 independent 1 ns long reactive molecular dynamics simulations of a pure water slab and of a slab of water with one excess proton (at an effective concentration of approximately 0.3 mol/L; see Supporting Information) are propagated using a neural network potential (NNP). This NNP was constructed as part of our recent study of water self-dissociation using the DeePMD-kit software , to reproduce the hybrid functional revPBE0-D3 level of theory. Because this network was trained to describe proton exchanges, our trajectory is reactive.…”
mentioning
confidence: 99%
See 1 more Smart Citation